A combined lipidomic and 16S rRNA gene amplicon sequencing approach reveals archaeal sources of intact polar lipids in the stratified Black Sea water column. Issue 1 (3rd October 2018) - Sollai, Martina; Villanueva, Laura; Hopmans, Ellen C.; Reichart, Gert‐Jan; Sinninghe Damsté, Jaap S.
Abstract: Archaea are important players in marine biogeochemical cycles, and their membrane lipids are useful biomarkers in environmental and geobiological studies. However, many archaeal groups remain uncultured and their lipid composition unknown. Here, we aim to expand the knowledge on archaeal lipid biomarkers and determine the potential sources of those lipids in the water column of the euxinic Black Sea. The archaeal community was evaluated by 16S rRNA gene amplicon sequencing and by quantitative PCR. The archaeal intact polar lipids (IPLs) were investigated by ultra‐high‐pressure liquid chromatography coupled to high‐resolution mass spectrometry. Our study revealed both a complex archaeal community and large changes with water depth in the IPL assemblages. In the oxic/upper suboxic waters (<105 m), the archaeal community was dominated by marine group (MG) I Thaumarchaeota, coinciding with a higher relative abundance of hexose phosphohexose crenarchaeol, a known marker for Thaumarchaeota. In the suboxic waters (80–110 m), MGI Nitrosopumilus sp. dominated and produced predominantly monohexose glycerol dibiphytanyl glycerol tetraethers (GDGTs) and hydroxy‐GDGTs. Two clades of MGII Euryarchaeota were present in the oxic and upper suboxic zones in much lower abundances, preventing the detection of their specific IPLs. In the deep sulfidic waters (>110 m), archaea belonging to the DPANN Woesearchaeota, Bathyarchaeota, and ANME‐1b clades dominated. Correlation analyses suggest that the IPLs GDGT‐0, GDGT‐1, and GDGT‐2 with two phosphatidylglycerol (PG) head groups and archaeol with a PG, phosphatidylethanolamine, and phosphatidylserine head groups were produced by ANME‐1b archaea. Bathyarchaeota represented 55% of the archaea in the deeper part of the euxinic zone and likely produces archaeol with phospho‐dihexose and hexose‐glucuronic acid head groups.